2014
DOI: 10.1590/s1516-89132014005000004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolysis and digestion in vitro on the activity of bovine plasma hydrolysates as inhibitors of the angiotensin I converting enzyme

Abstract: The angiotensin I-converting enzyme (ACE) inhibiting activity of bovine plasma hydrolyzates obtained by Alcalase 2.4 L at different degrees of hydrolysis (DH) was evaluated. For the evaluation of ACE inhibition (ACEI), HippurylHis-Leu was used as substrate and the amount of hippuric acid liberated by non-inhibiting ACE was determined by spectrophotometry at 228 nm. The results showed that the enzymatic hydrolysis increased the ACEI activity as compared with the un-hydrolyzed plasma. The highest activity was on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In this study, the results showed that peptides with the highest angiotensin I-converting enzyme inhibition activities were produced after five hours of hydrolysis, using 10% Alcalase enzyme [510]. In another research, hydrolysates from bovine plasma were obtained by Alcalase at different degrees of hydrolysis [511]. The highest angiotensin I-converting enzyme inhibition activity was obtained with a hydrolysis degree of 6.7%.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 73%
“…In this study, the results showed that peptides with the highest angiotensin I-converting enzyme inhibition activities were produced after five hours of hydrolysis, using 10% Alcalase enzyme [510]. In another research, hydrolysates from bovine plasma were obtained by Alcalase at different degrees of hydrolysis [511]. The highest angiotensin I-converting enzyme inhibition activity was obtained with a hydrolysis degree of 6.7%.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 73%
“… Deng et al. (2014) reported that porcine hemoglobin hydrolyzed by pepsin exhibited the highest ACE-inhibitory activity at a 9.3%DH, whereas Sampedro and Montoya (2014) found that bovine plasma hydrolysates obtained from Alcalase 2.4 L showed the maximum ACE-inhibitory activity of 50.2% at a 6.7% DH. The porcine BC hydrolyzed by a mixture of thermolysin, chymotrypsin, and trypsin also had an IC 50 value for ACE-inhibitory activity of 0.58 mg/mL ( Wei and Chiang, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACE-inhibitory peptides of the BCH-III digesta could play an important role in the antihypertensive effect. The digesta of bovine plasma and porcine globin also showed an ACE inhibition that was compared with that of their parent hydrolysates ( Yu et al., 2006 ; Sampedro and Montoya, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ACE inhibitory peptides have been isolated from food proteins, such as bone protein (Cheng et al, 2008), soya protein (Rho et al, 2009), pea protein (Barbana & Boye, 2010), bovine plasma (Sampedro & Montoya, 2014) and skate skin (Ngo et al, 2014). Proteases such as neutral protease, alcalase, papain, flavourzyme and bromelain are frequently used in the hydrolysis to produce ACE inhibitory peptides (Qu et al, 2010;Deng et al, 2014;Mohtar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%